2015
DOI: 10.1186/s13071-015-0866-6
|View full text |Cite
|
Sign up to set email alerts
|

An improved odor bait for monitoring populations of Aedes aegypti-vectors of dengue and chikungunya viruses in Kenya

Abstract: BackgroundEffective surveillance and estimation of the biting fraction of Aedes aegypti is critical for accurate determination of the extent of virus transmission during outbreaks and inter-epidemic periods of dengue and chikungunya fever. Here, we describe the development and use of synthetic human odor baits for improved sampling of adult Ae. aegypti, in two dengue and chikungunya fevers endemic areas in Kenya; Kilifi and Busia counties.MethodsWe collected volatiles from the feet and trunks of two female and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…aegypti and Ae. albopictus males using BG-Sentinel traps baited with CO 2 , MB5 blend or BG-Lure [17,23,47,48,53]. These findings are not surprising.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…aegypti and Ae. albopictus males using BG-Sentinel traps baited with CO 2 , MB5 blend or BG-Lure [17,23,47,48,53]. These findings are not surprising.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, studies from Owino et al [47,48] showed that the BG-Lure is not the most effective bait for Aedes aegypti compared to natural human odours and hexanoic acid. Our results and those from Owino et al [47,48] challenge the current view on capturing Aedes mosquitoes in which the BG-Sentinel trap in combination with the BG-Lure as attractant is considered the gold standard [23][24][25]. A possible reason for the reduced captures using the BG-Lure is that the airflow of the BG-Sentinel is less optimal for the cartridge design of the BG-Lure and odours are thus expelled more efficiently by the BG-Bowl.…”
Section: Discussionmentioning
confidence: 97%
“…For example, many mosquito species have an inherent preference for a specific host (e.g. a preference [26] Phenol [11,40] CO 2 [11,19,61] Terpineol [96] 2,2,6-Trimethylcyclohexane-1,4-dione a [26] p-Cresol [40] Lactic acid [11]/(S)-lactic acid [9,19] Geraniol [96] 1-(4-Ethylphenyl) ethanone a [26] 3-Methylindole (skatole) [40] (R)-1-Octen-3-ol [69,111] Eugenol [96] CHs b : Me-C 29 , n-heptadecane, n-pentacosane, n-hexacosane c…”
Section: Semiochemicals As Identified During the Different Mosquito Lmentioning
confidence: 99%
“…Previous work has found improved mosquito catches to specific host constituents as attractants than blends or crude volatiles [8,25], perhaps reflecting the need for additional research to design improved lures.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes including Aedes (Stegomyia) rely on olfactory cues to locate vertebrate hosts for a blood meal. Previous work has identified vertebrate host chemicals mainly from humans that attract mosquitoes [7,8]. The attractive cues are of practical and epidemiologic relevance and have been exploited in disease vector control and/or surveillance [9][10][11].…”
Section: Introductionmentioning
confidence: 99%